Factors Affecting Burnout Syndrome in Nurses - Muhamad Nor Mudhofar; Yoanita Hijriyati (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Burnout syndrome among nurses in hospitals can negatively impact the quality of healthcare services and the well-being of medical personnel. Dr. Rasidin Hospital in Padang faces challenges in improving service quality due to the high level of fatigue experienced by nurses. This study aimed to identify factors influencing burnout syndrome among nurses in the hospital. This research used a quantitative method with a cross-sectional design. The study was conducted at Dr. Rasidin Hospital, involving 100 nurses selected through simple random sampling. Data were collected using questionnaires measuring burnout syndrome, workload, working hours, and social support. Data analysis included univariate tests to describe frequency distributions and bivariate analysis using the Chi-Square test to examine relationships between variables. The results showed that 63% of nurses experienced burnout syndrome. Furthermore, 50% of nurses reported a very high workload, 47% worked more than 8 hours per day, and 40% perceived low social support. Bivariate analysis revealed significant relationships between workload (p = 0.004), working hours (p = 0.003), and social support (p = 0.025) with burnout syndrome. In conclusion, burnout syndrome among nurses is influenced by excessive workload, long working hours, and lack of social support. Therefore, hospital management should regulate workload and enhance social support to reduce burnout risk.